Effect of a mass media campaign on ambulance use for chest pain - Nehme, Z.; Cameron, P.; Akram, M.; Patsamanis, H.; Bray, Janet; Meredith, I.; Smith, K. (Australasian Medical Publishing, 2017)
© 2017 AMPCo Pty Ltd. Produced with Elsevier B.V. All rights reserved.Objectives: To evaluate the impact of comprehensive public awareness campaigns by the National Heart Foundation of Australia on emergency medical service (EMS) use by people with chest pain. Design, setting and participants: A retrospective analysis of 253 428 emergency ambulance attendances for non-traumatic chest pain in Melbourne, January 2008 e December 2013. Time series analyses, adjusted for underlying trend and seasonal effects, assessed the impact of mass media campaigns on EMS use. Main outcome measure: Monthly ambulance attendances. Results: The median number of monthly ambulance attendances for chest pain was 3609 (IQR, 3011e3891), but was higher in campaign months than in non-campaign months (3880 v 3234, P < 0.001). After adjustments, campaign activity was associated with a 10.7% increase (95% CI, 6.5e14.9%; P < 0.001) in monthly ambulance use for chest pain, and a 15.4% increase (95% CI, 10.1e20.9%; P < 0.001) when the two-month lag periods were included. Clinical presentations for suspected acute coronary syndromes, as determined by paramedics, increased by 11.3% (95% CI, 6.9e15.9%; P < 0.001) during campaigns. Although the number of patients transported to hospital by ambulance increased by 10.0% (95% CI, 6.1e14.2%; P < 0.001) during campaign months, the number of patients not transported to hospital also increased, by 13.9% (95% CI, 8.3e19.8%; P < 0.001). Conclusion: A public awareness campaign about responding to prodromal acute myocardial infarction symptoms was associated with an increase in EMS use by people with chest pain and suspected acute coronary syndromes. Campaign activity may also lead to increased EMS use in low risk populations.